Formation of Adult Education Policy: Key messages and main challenges - Ioannou, Nicoletta (Adult Education Critical Issues, 2023)
This article analyses the main influences and factors that affected adult education policy formation in the European Union (EU) and the key messages as well as leading directions and related key concepts identified in the European policy documents that are presented. In order to investigate the above, a review of official EU policy documents on adult education over the last twenty years was undertaken. Adult education gained a prominent position in EU policy as a vital component of lifelong learning; however, the emphasis has mostly been on realizing its economic goals, by focusing on labour market trends and needs, such as employability and competitiveness. This article takes the position that adult education policies should ensure seamless participation of adults in learning so as to promote the personal and social development and the wellbeing of adults and creatively contribute to the formation of more cohesive and just societies.